PENGETAHUAN IBU BALITA TENTANG STUNTING DI KELURAHAN PEKAN TANJUNG MORAWA - Sidabuke, Idaria; Parapat, Friska; Lumbantoruan, Mestika (JURNAL HEALTH REPRODUCTIVE, 2021)
The results of the Study on the Nutritional Status of Indonesian Toddlers (SSGBI) in 2019 showed the prevalence rate of stunting under five in 2013 was 37.2%, decreased by 6.4% in 2018 which was 30.8% and continued to decline by 3.1% in 2019, namely 27.67%. Another factor that is interrelated with this case is the knowledge of the mother and family regarding stunting, both in terms of knowledge of the meaning, causes, impacts, prevention and prevention of stunting itself. This study uses a descriptive design to see a description of the knowledge of mothers who have toddlers about stunting. The population of this research is mothers who have toddlers aged 12-59 months in Pekan Tanjung Morawa Village with a sample size of 66 people (total sampling). The results of the study found that the majority of respondents had less knowledge about stunting (68%) in Pekan Tanjung Morawa Village. It is expected that respondents can increase mother's knowledge about stunting, respondents can further increase their knowledge of stunting through health worker facilities, or existing books so that they can prevent stunting cases in infants and toddlers.